If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(3x-7)=x+5
We move all terms to the left:
4(3x-7)-(x+5)=0
We multiply parentheses
12x-(x+5)-28=0
We get rid of parentheses
12x-x-5-28=0
We add all the numbers together, and all the variables
11x-33=0
We move all terms containing x to the left, all other terms to the right
11x=33
x=33/11
x=3
| -5=-2(3-7x) | | t^2-100t-50=0 | | 30=3*x | | 4z=360 | | -5=2(3-7x) | | 19=x/12+16 | | 12z-40=360 | | 16z-40=360 | | 199=9+10v | | 14x+5=4x | | 14x+5=8x | | r^2-20r+16=0 | | 8=-2n+4n | | 12z+50=180 | | F(x)=-0-7 | | r2-20r+16=0 | | F(x)=-3-7 | | F(x)=-5-7 | | 3(x+1)-5+3x=10 | | 10/p=11.696/16.202 | | 3x+(2x+10)=100 | | F(x)=-7-7 | | 7x+3(-1-7x)+4x=-23 | | -6x-9=4(5-x) | | 12z-40=180 | | 36.49=7g+3.73 | | 27=7-3(2x+5)-x | | 2b+3-5b=-2-2(1-b) | | 0.08x+(0.18)(3)=0.12(x+3) | | 1.36g-4=0.76 | | 12y=-2y+224 | | 2x=20=3x=5 |